Design of a microstrip patch antenna using low temperature co-fired ceramic technology - Mohd Natashah, Norizan; Muammar, Mohamad Isa; Soh, Ping Jack; Azremi, Abdullah Al Hadi; Norhawati, Aahmad (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org